The Association of Financial Distress With Disability in Orthopaedic Surgery. Issue 11 (1st June 2019) - Mertz, Kevin; Eppler, Sara L.; Thomas, Kevin; Alokozai, Aaron; Yao, Jeffrey; Amanatullah, Derek F.; Chou, Loretta; Wood, Kirkham B.; Safran, Marc; Steffner, Robert; Gardner, Michael; Kamal, Robin N.
Abstract : Introduction: Increased out-of-pocket costs have led to patients bearing more of the financial burden for their care. Previous work has shown that financial burden and distress can affect outcomes, symptoms, satisfaction, and adherence to treatment. We asked the following questions: (1) Does patients' financial distress correlate with disability in patients with nonacute orthopaedic conditions? (2) Do patient demographic factors affect this correlation? Methods: We conducted a cross-sectional, observational study of new patients presenting to a multispecialty orthopaedic clinic with a nonacute orthopaedic complication. Patients completed a demographics questionnaire, the InCharge Financial Distress/Financial Well-Being Scale, and the Health Assessment Questionnaire Disability Index. Statistical analysis was done using Pearson's correlation. Results: The mean score for financial distress was 4.10 (SD, 2.09; scale 1 [low distress] to 10 [high distress]; range, 1.13 to 10.0), and the mean disability score was 0.54 (SD, 0.65; scale 0 to 3; range, 0 to 2.75). A moderate positive correlation exists between financial distress and disability (r = 0.43; P < 0.01). Financial distress and disability were highest for poor, uneducated, Medicare patients. Conclusions: A moderate correlation exists between financial distress and disability in patients with nonacute orthopaedic conditions, particularly in patients with low socioeconomic status. Orthopaedic surgeons may benefit from identifying patients in financial distress and discussing the cost of treatment because of its association with disability and potentially inferior outcomes. Further investigation is needed to test whether decreasing financial distress decreases disability. Level of Evidence: Level III prospective cohort